Analisa Pengendalian Produk Cacat Pada Sepatu di UD. XYZ Menggunakan Metode Statistical Quality Control - Moh. Ainul Fais; I. G. A. Sri Deviyanti; Silvana Mohamad; Devi Susiati (Industrial & System Engineering Journals (ISEJOU), 2023)
The progress of the shoe industry in Indonesia has encouraged small and large shoe entrepreneurs to compete in terms of quality, because consumers are very dependent on quality, so good quality control is needed in order to make consumers loyal customers. UD. XYZ is a small company that has problems with quality control so it really needs quality control using the SQC method. And the result was that UD. XYZ that the P control chart data shows that none of the 30 points are outside the control limits, so it can be concluded that the process is under control, but UD. XYZ still has to improve product quality by evaluating 4 elements (machines, people, tools, and methods).